Pengaruh Budaya Organisasi Dan Komunikasi Terhadap Kinerja Pengurus Organisasi Mahasiswa Dengan Komitmen Organisasi Sebagai Variabel Intervening ( Studi Pada UKM Seni Islami Universitas Islam Malang ) - Bima Nufrizar Rosyidi; Abdul Kodir Djaelani; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract Efficient and fast smooth running and satisfying human needs is very important in the life of an enterprise if the people managing it have technical managerial and human skills. Thus organizations need human resources (HR) for organizational change, one of which is Student Creative Unit (UKM). UKM Islamic Art is a student activity unit and a forum for students to develop their talents in the field of Islamic art and to shape the personality of the organization. But due to the lack of frequent communication between members the ability to reach members to participate in active activities in the organization or the members lack of confidence in expressing their opinions in the forum there are still many obstacles to the development of the organization. Lack of understanding of the work of the Council at Unisma Islamic Arts UKM and lack of confidence in the Governor and the Council does not make enhancing productivity a priority. This study used a non-probability sampling method with 66 samples. The results of this study show that organizational commitment cannot mediate the influence between organizational culture and organizational communication on management effectiveness. This means that high or low levels of organizational commitment do not influence the impact of organizational culture and communication on the growth and decline of Islamic artistic behaviour. Keywords: Organizational Culture, Organizational Communication, Organizational Commitment, Management Performance